Chemical Synthesis of Phosphorylated Histone H2A at Tyr57 Reveals Insight into the Inhibition Mode of the SAGA Deubiquitinating Module. Issue 16 (9th March 2016) - Jbara, Muhammad; Maity, Suman Kumar; Morgan, Michael; Wolberger, Cynthia; Brik, Ashraf
Abstract: Monoubiquitination of histone H2B plays a central role in transcription activation and is required for downstream histone‐methylation events. Deubiquitination of H2B by the Spt‐Ada‐Gcn5 acetyltransferase (SAGA) coactivator complex is regulated by a recently discovered histone mark, phosphorylated H2AY57 (H2AY57p), which inhibits deubiquitination of H2B by the SAGA complex as well as restricting demethylation of H3 and increasing its acetylation. Evidence for the effect of H2AY57p, however, was indirect and was investigated in vivo by monitoring the effects of chemical inhibition of Tyr kinase CK2 or by mutating the phosphorylation site. We applied the total chemical synthesis of proteins to prepare H2AY57p efficiently and study the molecular details of this regulation. This analogue, together with semisynthetically prepared ubiquitinated H2B, enabled us to provide direct evidence for the cross‐talk between those two marks and the inhibition of SAGA activity by H2AY57p. Abstract : Two in one : Total chemical synthesis by the connection of three fragments via two consecutive ligation reactions carried out in a one‐pot manner provided histone protein H2A homogeneously phosphorylated at Tyr 57 (see scheme). The assembly of phosphorylated H2A and ubiquitinated H2B with histone proteins H3 and H4 into a nucleosome provided direct evidence for the inhibition of the activity of the SAGA complex known to cleave ubiquitin from H2B.